PERAN PROSES REKRUTMEN DAN SELEKSI DALAM MEMBANGUN TENAGA KERJA KOMPETEN: STUDI MAGANG DI PT VICTORY INTERNATIONAL FUTURES - Abdullah, Abdullah; Irbayuni, Sulastri (Bussman Journal : Indonesian Journal of Business and Management, 2025)
Recruitment and selection are crucial processes in human resource management that play a vital role in ensuring the quality of the workforce recruited by a company. PT Victory International Futures, as a futures brokerage company, implements active and adaptive recruitment strategies through various digital media such as social media and a Customer Relationship Management (CRM) system. According to Simamora (2006), effective recruitment aims to attract potential candidates who meet the organization’s needs. This is supported by Rivai (2015), who states that proper selection determines the long-term success of a company. This study uses observation and hands-on practice during the internship at PT Victory International Futures. The findings show that the recruitment and selection processes implemented by the company enhance candidate quality through direct approaches such as canvassing, digital promotion, and orientation training. Moreover, the use of technology in managing candidate data supports the efficiency of the selection process. These findings support Dessler’s (2020) view that integrating technology into HR processes can accelerate recruitment and improve accuracy in employee selection. Thus, a structured recruitment and selection practice contributes to developing a competent workforce ready to compete in the futures trading industry.